MODEL PEMBELAJARAN QUANTUM DI MA AL-IRSYAD LALONGGASUMEETO KABUPATEN KONAWE - Khrisman, Muh; Mania, Sitti; Safei (Istiqra: jurnal hasil penelitian, 2023)
One quality learning model is the quantum learning model, this learning model can provide knowledge to students. Therefore, this research aims to find out and understand how the quantum learning model is implemented at MA Al-Irsyad Lalonggasumeeto, Konawe Regency. This research is qualitative research with a qualitative descriptive approach using interview, observation, and documentation data collection techniques. In contrast, the data analysis used is data reduction techniques, data display, checking the validity of the data through triangulation, and then concluding. The research results show that the quantum learning model applied by teachers can improve the quality of students’ learning at Al-Irsyad Lalonggasumeeto Madrasah, Konawe Regency. At the same time, it can provide a solution to the main cause of the low quality of learning at Madrasah Al-Irsyad Lalonggasumeeto, Konawe Regency, so that the learning achievement of each student can be increased. As student achievement increases, a teacher’s achievement increases in preparing plans or patterns used in conducting learning. This increase in achievement is directly proportional to his ability to utilize technology in the learning process at MA Al-Irsyad Lalonggasumeeto Konawe Regency